2018
DOI: 10.1039/c8gc00069g
|View full text |Cite
|
Sign up to set email alerts
|

Transition-metal-free C–N and C–C formation: synthesis of benzo[4,5]imidazo[1,2-a]pyridines and 2-pyridones from ynones

Abstract: We have developed a facile method for the synthesis of benzo[4,5]imidazo[1,2-a]pyridines and 2-pyridones from readily available ynones and 2-methylbenzimidazoles or acetamides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 89 publications
0
23
0
Order By: Relevance
“…Based on the abovementioned experimental results and the related literature, 17,18,26,37 a plausible reaction mechanistic pathway is proposed in Scheme 4. Initially, under the action of a base, the nucleophilic substitution reaction of 2 with muco-bromic acid 1a generates intermediate A .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the abovementioned experimental results and the related literature, 17,18,26,37 a plausible reaction mechanistic pathway is proposed in Scheme 4. Initially, under the action of a base, the nucleophilic substitution reaction of 2 with muco-bromic acid 1a generates intermediate A .…”
Section: Resultsmentioning
confidence: 99%
“…Initially, under the action of a base, the nucleophilic substitution reaction of 2 with muco-bromic acid 1a generates intermediate A . 17 Secondly, decarboxylation takes place to give B . 26 Then, intermediate B can react with another NH-containing heterocyclic nucleophile ( 2 or 3 ) to give the intermediate C by Michael addition, and C undergoes a base-promoted dehydrohalogenation reaction to give intermediate D ( e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through transition‐metal‐catalyzed cyclization reaction of N ‐aryl‐2‐aminopyridines with benzyl acrylate, Li et al reported a Rh(III)‐catalyzed oxidative coupling reaction to produce the corresponding products in the presence of Cu(OAc) 2 in DMF at 100 °C for 12 h (Scheme 1b) [9] . Following that, a number of methods for the same purpose were developed through the cyclization reaction of N ‐aryl‐2‐aminopyridine with alkynes, [10] 2‐aminopyridine with acetaldehydes [11] or N ‐acetyl‐2‐aminopyridine with ynones [12] . However, the use of transition‐metal complexes, relatively inconvenient reaction conditions and uncommonly used starting materials greatly limited the application of these strategies.…”
Section: Methodsmentioning
confidence: 99%